The Uniqueness of Acting Skills in the Art of Puppet Theater - Bakhora, Djumamuratova; A’zamjon, Abdukhalilov (Research Parks Publishing LLC, 2023)
This article is about specific approaches to professional training of puppet theater actors as a type of theater art.